1991
DOI: 10.1136/jnnp.54.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behaviour therapy in chronic fatigue syndrome.

Abstract: Fifty patients fulfilling operational criteria for the chronic fatigue syndrome (CFS), and who had been ill for a mean of five years, were offered cognitive behaviour therapy in an open trial. Those fulfilling operational criteria for depressive illness were also offered tricyclic antidepressants. The rationale was that a distinction be drawn between factors that precipitate the illness and those that perpetuate it. Among the latter are cognitive factors such as the belief that physical symptoms always imply t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
2
12

Year Published

1995
1995
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(155 citation statements)
references
References 27 publications
6
135
2
12
Order By: Relevance
“…The very issue of providing a diagnosis that is acceptable to the afflicted individual gives rise to controversy (Brown, 1995). While sorne report that having a diagnosis helps individuals cope with feeling unwell (Woodward, 1993), other evidence suggests that reinforcing the notion that medically unexplained symptoms are biological in origin may be implicated in the chronicity of the disorder (Butler et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The very issue of providing a diagnosis that is acceptable to the afflicted individual gives rise to controversy (Brown, 1995). While sorne report that having a diagnosis helps individuals cope with feeling unwell (Woodward, 1993), other evidence suggests that reinforcing the notion that medically unexplained symptoms are biological in origin may be implicated in the chronicity of the disorder (Butler et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue Questionnaire (FQ) was originally developed for a hospital study of Chronic Fatigue Syndrome, 21,22 and was later re®ned in a validation study. 23 The FQ measures fatigue speci®cally and the questionnaire is intended for the detection of fatigue cases in epidemiological studies.…”
Section: Methodsmentioning
confidence: 99%
“…The final trigger or precipitator may be any of the above. The perpetuators are the development of patterns of illness in response to the symptoms, stress and/ or recurrent infection (Butler et al, 1991;Sharpe, 1991) and are discussed in more detail below.…”
Section: The Process Of Assessmentmentioning
confidence: 99%
“…The programme is based on OT theory and encompasses the bio-psychosocial model (Wessely, 1992;Hagedorn, 1995;Sharpe et al, 1997) using the principles of cognitive behaviour therapy Sharpe, 1991;Cox and Findley, 1998) and graded activity (Butler et al, 1991;Sharpe et al, 1997;Cox and Findley, 1998). Randomized controlled trials have suggested that cognitive behaviour therapy (Sharpe et al, 1996;Deale et al, 1997) and graded exercise therapy (Fulcher and White, 1997) may be useful treatments in the outpatient management of CFS.…”
Section: The Occupational Therapy Programmementioning
confidence: 99%